2006
DOI: 10.1074/mcp.m600180-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Testicular Receptor 4 Activity by Mitogen-activated Protein Kinase-mediated Phosphorylation

Abstract: Testicular receptor 4 (TR4) is an orphan member of the nuclear receptor superfamily. Despite the lack of identified ligands, its functional role has been demonstrated both in animals and cell cultures. However, it remains unclear how the biological activity of TR4 is regulated without specific ligands. In this study, we showed that in the absence of specific ligands the activity of TR4 could be modulated by mitogen-activated protein kinase (MAPK)-mediated phosphorylation of its activation function 1 (AF-1) dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…It has been reported that various signals such as MAPK/extracellular signal-related kinase (ERK) plays an important role as a signaling mediator for various nuclear receptors including TR4 (Chen et al, 2005;Huq et al, 2006). Early study showed that TR4 can be phosphorylated by MAPK and this phosphorylation reduces TR4 activity (Huq et al, 2006). Interestingly, CLA is involved in various signaling pathways including MAPK/ ERK (Chung et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that various signals such as MAPK/extracellular signal-related kinase (ERK) plays an important role as a signaling mediator for various nuclear receptors including TR4 (Chen et al, 2005;Huq et al, 2006). Early study showed that TR4 can be phosphorylated by MAPK and this phosphorylation reduces TR4 activity (Huq et al, 2006). Interestingly, CLA is involved in various signaling pathways including MAPK/ ERK (Chung et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, we found that CLA consistently inhibited TR4 transcriptional activity when we used different reporter genes fused with different DR1 sequences, indicating that CLA is a functional modulator of TR4 activity. It has been reported that various signals such as MAPK/extracellular signal-related kinase (ERK) plays an important role as a signaling mediator for various nuclear receptors including TR4 (Chen et al, 2005;Huq et al, 2006). Early study showed that TR4 can be phosphorylated by MAPK and this phosphorylation reduces TR4 activity (Huq et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…TR4 functions as a repressor when MAPK mediates the phosphorylation of the AF1 domain through the preferential recruitment of corepressor RIP140. In contrast, TR4 functions as an activator when its AF1 domain is dephosphorylated due to its selective recruitment of the coactivator PCAF (Huq et al 2006). However, the potential physiological consequences of these MAPK phosphorylations of TR4 remain unclear.…”
Section: Phosphorylationmentioning
confidence: 99%
“…TR4 could also be phosphorylated by MAPK at its AF1 domain in the absence of specific ligands (Huq et al 2006). MAPK activation by anisomycin causes a nearly complete loss of TR4 transactivation.…”
Section: Phosphorylationmentioning
confidence: 99%
See 1 more Smart Citation